Working memory training in children with developmental language disorder: Effects on complex syntax in narratives - Delage, Hélène; Stanford, Emily; Baratti, Clara; Durrleman, Stéphanie (Frontiers in Rehabilitation Sciences, 2023)
This study assesses the impact of a working memory training program on the syntactic complexity of the spontaneous speech of French-speaking children with Developmental Language Disorder (DLD). Thirty-nine 6- to 12-year-old children with DLD were allocated to a WM training (DLDMM, N = 20) or an active control group (DLDSQULA, N = 19). The computerized training sessions took place three times a week, yielding 12 training hours per participant. Syntactic complexity was assessed in storytelling, measuring mean length of utterances, use of embedded clauses and rate of errors in complex utterances. The performance of participants with DLD was first compared to previous spontaneous data of 40 typically-developing (TD) children of the same age. Then, intragroup (pre- vs. post-test) and intergroup (DLDMM vs. DLDSQULA) comparisons were made to assess the impact of the working memory training on the language measures. Global results confirmed syntactic impairment in children with DLD, as opposed to TD children, with large differences for the use of embedded clauses. Findings also suggested gains in the mastery of embedded clauses in children who participated in the WM training, whereas no gains were observed in the DLD control group. These findings confirm deficits in complex syntax in children with DLD, in particular in embedded clauses, and may encourage the clinical use of language sample analysis, which provides an ecological account of children's language performance. While our results should be replicated on a larger scale, they also suggest positive transfer effects of working memory training on the capacity of participants with DLD to produce embedded clauses, in line with previous studies showing a positive effect of WM training on tasks of expressive syntax. It thus seems that working memory training can yield benefits for language, which leaves open the door to new therapeutic approaches for children with DLD.